Effects of preharvest treatment, disinfections, packaging and storage environment on quality of tomato - Workneh, T. S. (Springer-Verlag, 2011)
The major objective of this study was to explore the significance of an integrated agro technology in maintenance of postharvest quality of tomato. Preharvest ComCat® treated tomatoes and untreated controls were evaluated for changes in physiological, chemical, and microbiological quality during storage at 13 °C and room temperature (16.9–25.2 °C) and a relative humidity of 34–76%. Effects of disinfection coupled with packaging were evaluated. Physiological weight loss, total soluble solids, peroxidase activity and marketability were maintained better in anolyte disinfected tomatoes. At harvest, ComCat® treated tomatoes had lower pH, glucose and microbial populations, and higher total soluble solids, total titratable acids, sucrose, peroxidase activity than controls. The total soluble solids were better retained in ComCat® treated tomatoes than in control, while the sucrose and glucose contents remained lower after ripening. Peroxidase activities were lower in ripening ComCat® treated tomatoes, and difference in polygalactronase activity was only visible after 30 days. The microbial populations were lower in ComCat® treated fruit. Marketability of ComCat® treated tomatoes was better than that of the control. Integrated technology covering preharvest ComCat® application, disinfection with anolyte water and packaging combined with cold storage at 13 °C maintained the superior quality of tomato.